2018
DOI: 10.5194/acp-18-9767-2018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of aerosol radiative effects and their impact on clouds and atmospheric dynamics over southern West Africa

Abstract: Abstract. Southern West Africa (SWA) is undergoing rapid and significant socioeconomic changes associated with a massive increase in air pollution. Still, the impact of atmospheric pollutants, in particular that of aerosol particles, on weather and climate in this region is virtually unexplored. In this study, the regional-scale model framework COSMO-ART is applied to SWA for a summer monsoon process study on 2–3 July 2016 to assess the aerosol direct and indirect effect on clouds and atmospheric dynamics. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…() and Deetz et al . (). In this area models tend to overestimate clouds, associated with too dry and too cold conditions near the surface, particularly after the monsoon onset, when the main rain band has moved northwards towards the Sahel and when coastal upwelling is well established.…”
Section: Discussionmentioning
confidence: 97%
“…() and Deetz et al . (). In this area models tend to overestimate clouds, associated with too dry and too cold conditions near the surface, particularly after the monsoon onset, when the main rain band has moved northwards towards the Sahel and when coastal upwelling is well established.…”
Section: Discussionmentioning
confidence: 97%
“…Most of our knowledge on the processes relevant for LLCs is based on numerical simulations, as high-quality observational data are scarce in this region. Studies by Schrage and Fink (2012), Schuster et al (2013), Adler et al (2017) and Deetz et al (2018) suggest that processes spanning from the microscale to the synoptic scale are important such as horizontal cold air advection, orographic lifting, lifting related to gravity waves and shear-generated vertical mixing underneath the axis of a nocturnal low-level jet (LLJ). There is evidence that the horizontal cold air advection is related to the southwesterly monsoon flow, which transports maritime air from the Gulf of Guinea northwards over land.…”
Section: Introductionmentioning
confidence: 99%
“…They quantified the important impact of aerosol on shortwave radiation (a decrease of -20 W m −2 ) whereas the impact 70 on longwave radiation was found to be negligible. In the continuity of this work, Deetz et al (2018b) showed that the amount of aerosols over southern West Africa impacts the dynamics of the daytime coastal moist front generated along the Gulf of Guinea and the intensity of its inland propagation, this feature modulating the transport of anthropogenic aerosols emitted at the coast (Deroubaix et al, 2019).…”
mentioning
confidence: 88%